Anthranoxides as Highly Reactive Arynophiles for the Synthesis of Triptycenes. Issue 39 (11th June 2020) - Iwata, Takayuki; Hyodo, Mizuki; Fukami, Takuto; Shiota, Yoshihito; Yoshizawa, Kazunari; Shindo, Mitsuru
Abstract: We report herein an efficient method to synthesize triptycenes by the reaction of benzynes and anthranoxides, which are electron‐rich and readily prepared from the corresponding anthrones. Using this method, 1, 9‐ syn ‐substituted triptycenes were regioselectively obtained employing 3‐methoxybenzynes. This method was also applied to synthesize pentiptycenes. A DFT study revealed that the cycloaddition of lithium anthranoxide and benzyne proceeds stepwise. Abstract : An efficient method to synthesize triptycenes is reported by the reaction of benzynes and anthranoxides, which are electron‐rich and readily prepared from the corresponding anthrones (see scheme). 1, 9‐ syn ‐substituted triptycenes were regioselectively obtained employing 3‐methoxybenzynes. This method was also applied to synthesize pentiptycenes. A DFT study revealed that the cycloaddition of lithium anthranoxide and benzyne proceeds stepwise.